The gendered behaviors displayed by Disney protagonists - Clarke, Lucy L.; Hine, Benjamin; England, Dawn; Flew, Poppy P. M. S.; Alzahri, Ritaj; Juriansz, Stepheni N.; Garcia, Ma. J. B. C. (Frontiers in Sociology, 2024)
Previous research suggests that the portrayal of male and female protagonists in Disney animations may be changing over time. The current study examined the portrayal of gendered behaviors displayed within some of Disney's most successful animated feature length films, including those beyond the Disney princess franchise. Extending the scope of the Disney animated films analyzed was important because both young girls and young boys report little personal interest in male characters within the Disney princess animations. This suggests that it is important to look beyond the Disney princess franchise to understand the gendered behaviors displayed by potentially influential male Disney protagonists. The current study also considered a greater number of masculine and feminine behaviors as well as some gender-neutral traits which had yet to be incorporated. A quantitative content analysis of 39 Disney protagonists from films released between 1937 and 2021 was conducted. The results revealed that male and female protagonists were statistically higher in feminine than masculine traits. Female protagonists from the earliest animations were the most feminine. However, there was no statistical difference in the gendered portrayals of females in the animations released in the 1990s and those released from 2009 to 2021 suggesting some continued stereotyping in females' profiles. Alternatively, male characters were more feminine relatively consistently across time-points. This study concludes that Disney is persistently portraying stereotyped female protagonists, and this could have implications on young females' behavioral profiles. However, the extent to which feminine traits are being celebrated when displayed by male protagonists needs to be examined, as well as the potential relationship between such messages and boys' behaviors and children's conceptualizations of gender more broadly.